Numerical analysis of the thermoaeraulic behavior of air during the opening of the door of a refrigerated truck trailer equipped with cold plates. (April 2022) - Jeong, Jihyuk; Benchikh Le Hocine, Alla Eddine; Croquer, Sergio; Poncet, Sébastien; Michel, Benoit; Bonjour, Jocelyn
Abstract: The present work reports the numerical simulation of the heat transfer inside a refrigerated truck trailer equipped with three eutectic plates and fans. The numerical model solves the conjugated heat transfer inside the trailer under unsteady conditions. The conservation equations of mass, momentum and energy are solved in 3D and closed using the k- ω Shear Stress Transport (SST) model. It is first favorably validated against the numerical and experimental data of Lafaye de Micheaux et al. (2015). The results are then extended to investigate the performance of a refrigeration system equipped with eutectic plates for the transport of frozen food products. As no significant 3D effects are reported, a 2D model is adapted to analyze the configurations with the plates placed in series on the roof of the trailer or vertically at its back. During the door opening period, the configuration with the plates placed on the roof without the cargo leads to noticeably lower area-averaged temperatures inside the trailer than the configuration with the plates placed on the back due to the presence of recirculation zones and the cold plates located near the doorway. However, the presence of the cargo eliminates the formation of these zones that limits the infiltration of the outside atmospheric air. Also the configuration with the plates placed in the roof allows the outside atmospheric air to infiltrate earlier, resulting in an overall higher temperature observed for the cargo. Highlights: A CFD model of a refrigerated truck trailer with eutectic plates was developed. Heat infiltration was analyzed during the door opening period. Influence of eutectic plate locations and fan operating modes were investigated. Recirculation zones inside the trailer limited the infiltration. Presence of cargo eliminated the recirculation zones inside the trailer.